Persistence of innovation in Dutch manufacturing : is it spurious? - Wladimir Raymond; Pierre A. Mohnen; Franz Palm; Sybrand Schim van der Loeff (Center for Economic Studies and ifo Institute (CESifo), 2006)
This paper studies the persistence of innovation and the dynamics of innovation output in Dutch manufacturing using firm data from three waves of the Community Innovation Surveys (CIS), pertaining to the periods 1994-1996, 1996-1998, and 1998-2000. We estimate by maximum likelihood a dynamic panel data type 2 tobit model accounting for individual effects and handling the initial conditions problem. We find that there is no evidence of true persistence in achieving technological product or process innovations, while past shares of innovative sales condition, albeit to a small extent, current shares of innovative sales.
Keywords: C33; O31; C34; 330; dynamic panel data type 2 tobit; innovation; spurious persistence; Verarbeitendes Gewerbe; Innovation; Niederlande